2021
DOI: 10.3390/healthcare9030358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School-Based Exercise Program on Obesity and Physical Fitness of Urban Youth: A Quasi-Experiment

Abstract: (1) Purpose: The purpose of this study was to evaluate if an after-school intervention program could prevent obesity and promote the physical fitness of urban sedentary school children. (2) Methods: A 16-week after-school physical fitness program was provided to 36 middle school students (7th, 8th, and 9th graders) recruited from a middle school for three days a week. They were high-risk youth showing poor health status (level 4 or 5) in the regular physical fitness evaluation conducted. Their body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Especially noticeable were the changes seen in both male and female students in the final year of elementary school and the first year in middle school. A previous study by Song et al [ 25 ] reported significant improvement in flexibility (pre = 2.64 ± 3.49, post = 5.98 ± 2.78) through a 16-week health exercise program geared toward adolescents. Lee et al [ 24 ] also reported improved flexibility after a one-year physical activity program.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Especially noticeable were the changes seen in both male and female students in the final year of elementary school and the first year in middle school. A previous study by Song et al [ 25 ] reported significant improvement in flexibility (pre = 2.64 ± 3.49, post = 5.98 ± 2.78) through a 16-week health exercise program geared toward adolescents. Lee et al [ 24 ] also reported improved flexibility after a one-year physical activity program.…”
Section: Discussionmentioning
confidence: 97%
“…Considering this gap in the existing research, this study attempted to analyze changes in health-related physical fitness before and after the COVID-19 pandemic for elementary and middle school students in Korea using data obtained through the physical fitness promotion system (PAPS). Since 2010, all public and private schools in Korea have participated in the PAPS, which aims to evaluate physical fitness and provide exercise-related guidance to elementary, middle, and high school students based on assessments of physical factors such as power, flexibility, cardiorespiratory endurance, muscle endurance, and body composition [ 24 , 25 ]. The impact of PAPS has been assessed by various studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a Norwegian school-based intervention on physical activity resulted in increased PAL and improved physical fitness in adolescents, with an emphasis on cardiorespiratory fitness [23]. Similarly, after 16 weeks of physical activity promotion, Korean adolescents increased their physical fitness levels [24].…”
Section: Introductionmentioning
confidence: 99%
“… 91 Physical education programs at school are associated with reductions in children's cardiometabolic risk factors. 92 , 93 School-based primary care clinics reach over six million children annually in the U.S. and school nurses provide monitoring of children's chronic health conditions and support compliance with immunizations and routine primary care. 94 Households with children (especially young children) are at high risk of energy insecurity, and during periods of heat and cold, schools offer students eight or more hours of shelter from the elements.…”
Section: Inequities Of Basic Needs and Vital Services For Childrenmentioning
confidence: 99%